2017
DOI: 10.1161/circep.116.004614
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Posterior Left Atrial Adipose Tissue Mass and Atrial Fibrillation

Abstract: Background-Epicardial adipose tissue located close to the atrial wall can change the electric conduction of the left atrium, potentially leading to atrial fibrillation (AF). The aim of this study was to assess whether an increased atrial adipose tissue mass posterior to the left atrium is related to AF independent of demographical and cardiovascular risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 28 publications
(34 reference statements)
1
43
0
1
Order By: Relevance
“…Our results demonstrate that combined assessment of cine and noncontrast 3D Dixon provides better risk stratification to identify AF patients beyond both the clinical model and LA volume alone. This is supported by a CT study by van Rosendael et al, who reported that posterior LA fat measurement was useful for identifying AF patients . Thus, the integration of LA‐epicardial fat measurement may identify high‐risk populations of AF‐prone patients …”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Our results demonstrate that combined assessment of cine and noncontrast 3D Dixon provides better risk stratification to identify AF patients beyond both the clinical model and LA volume alone. This is supported by a CT study by van Rosendael et al, who reported that posterior LA fat measurement was useful for identifying AF patients . Thus, the integration of LA‐epicardial fat measurement may identify high‐risk populations of AF‐prone patients …”
Section: Discussionmentioning
confidence: 65%
“…This is supported by a CT study by van Rosendael et al, who reported that posterior LA fat measurement was useful for identifying AF patients. 32 Thus, the integration of LA-epicardial fat measurement may identify high-risk populations of AF-prone patients. 27 Our study has several limitations.…”
Section: Discussionmentioning
confidence: 99%
“…There is a particularly strong relationship between the size of the depot of posterior left atrial adipose tissue and the onset, persistence and recurrence of atrial fibrillation . Additionally, periatrial fat in patients with atrial fibrillation demonstrates genomic signatures that reflect activation of pro‐inflammatory and pro‐fibrotic pathways.…”
Section: Effect Of Epicardial Adipose Inflammation On the Atrial Myocmentioning
confidence: 99%
“…6 There is a particularly strong relationship between the size of the depot of posterior left atrial adipose tissue and the onset, persistence and recurrence of atrial fibrillation. 7 Additionally, periatrial fat in patients with atrial fibrillation demonstrates genomic signatures that reflect activation of pro-inflammatory and pro-fibrotic pathways. Of note, epicardial adipose tissue with the most severe structural and functional derangements resides in close proximity to myocardial foci with the greatest electrophysiological abnormalities.…”
Section: Effect Of Epicardial Adipose Inflammation On the Atrial Myocmentioning
confidence: 99%
“…Epicardial adipose tissue (EAT) is a metabolically active tissue located between the visceral pericardium and the epicardium, known as a risk factor for various cardiovascular diseases, 1 particularly atrial fibrillation (AF), to which EAT is closely related. EAT volume is related to both new‐onset AF 2,3 and AF recurrence after catheter ablation 4,5 or cardioversion 6 . Moreover, EAT alters the atrial electrophysiological properties contributing to generate AF 7,8 …”
Section: Introductionmentioning
confidence: 99%